The cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Coccomorpha: Pseudococcidae) arrives in India - Joshi, Sunil; Pai, Sachin G.; Deepthy, K.b.; Ballal, Chandish R.; Watson, Gillian W. (Zootaxa, 2020)
Invasive species threaten the ecological and economic wellbeing of a country (Pimentel et al. 2001). In the last decade, several mealybugs and soft scale insects have been accidentally introduced to India, of which some have become serious pests (e.g., Phenacoccus solenopsis Tinsley, Paracoccus marginatus Williams & Granara de Willink, Phenacoccus madeirensis Green and Pseudococcus jackbeardsleyi Gimpel & Miller); others are widening their host ranges and spreading rapidly. Kilifia acuminata (Signoret) and Protopulvinaria longivalvata Green seem relatively harmless but Trijuba oculata (Brain) and Pulvinaria urbicola Cockerell cause economic damage (Joshi & Rameshkumar 2013; Joshi 2017).